2004
DOI: 10.1523/jneurosci.2943-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Morphological Characterization of Dentate Granule Cells in the p35 Knock-Out Mouse Hippocampus: Evidence for an Epileptic Circuit

Abstract: There is a high correlation between pediatric epilepsies and neuronal migration disorders. What remains unclear is whether there are intrinsic features of the individual dysplastic cells that give rise to heightened seizure susceptibility, or whether these dysplastic cells contribute to seizure activity by establishing abnormal circuits that alter the balance of inhibition and excitation. Mice lacking a functional p35 gene provide an ideal model in which to address these questions, because these knock-out anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 58 publications
(77 reference statements)
6
70
1
Order By: Relevance
“…Consistent with these reports, our results suggest that mossy fibers in LIS1 mutants exhibit relatively normal axonal projections toward area CA3. Moreover, we did not find evidence for polysynaptic responses to afferent stimulations or the types of epileptiform burst discharges that accompany recurrent mossy fiber circuits in any mature or newborn granule cell as reported for acquired epilepsy models (Wuarin and Dudek, 2001;Hunt et al, 2009Hunt et al, , 2010 or other models of neuronal migration disorder (Wenzel et al, 2001;Patel et al, 2004;Kwon et al, 2006;Patrylo and Willingham, 2007). Therefore, mossy fiber sprouting does not appear to be a contributing factor to the pathology of LIS1 haploinsufficiency, despite significant granule cell displacement, hyperexcitability, and spontaneous seizures in LIS1 mutant mice.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Consistent with these reports, our results suggest that mossy fibers in LIS1 mutants exhibit relatively normal axonal projections toward area CA3. Moreover, we did not find evidence for polysynaptic responses to afferent stimulations or the types of epileptiform burst discharges that accompany recurrent mossy fiber circuits in any mature or newborn granule cell as reported for acquired epilepsy models (Wuarin and Dudek, 2001;Hunt et al, 2009Hunt et al, , 2010 or other models of neuronal migration disorder (Wenzel et al, 2001;Patel et al, 2004;Kwon et al, 2006;Patrylo and Willingham, 2007). Therefore, mossy fiber sprouting does not appear to be a contributing factor to the pathology of LIS1 haploinsufficiency, despite significant granule cell displacement, hyperexcitability, and spontaneous seizures in LIS1 mutant mice.…”
Section: Discussioncontrasting
confidence: 56%
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Pafah1b1 mutants probably represent different seizure pathogenesis from Dcx; Dclk2 nulls or other epilepsy models showing a decrease of IPSC frequency. The p35 (cdk5r1) nulls display severe dyslamination of pyramidal and granule cell neurons that contribute to seizure activity by forming an abnormal excitatory feedback circuit (19). Thus, the mechanisms underlying epilepsy are gene-specific, but point to the importance of lamination and dendritic maturation in hippocampal development.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, interneurons expressing gammaaminobutyric acid (GABA), the principal inhibitory neurotransmitter in the human brain, are essential for normal neuronal synchronization and maintenance of a seizure threshold in humans (Cossette et al 2002), rodents (Delorey et al 1998), and zebrafish (Baraban et al 2005). A failure of the brain to properly regulate neuronal synchrony can result from ion channel defects (Xu and Clancy 2008), neuropeptide depletion (Brill et al 2006), brain malformations (Patel et al 2004), interneuron loss (Cobos et al 2005), and/or synaptic vesicle recycling failure (Di Paolo et al 2002), all of which may be caused by disrupting the nerve-cell cytoskeleton. Therefore, further exploration of putative links between cytoskeletal components and neurotransmission may accelerate development of novel therapeutics for epilepsy.…”
mentioning
confidence: 99%